2015
DOI: 10.1111/ijd.12925
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tacrolimus and clobetasol in the treatment of oral lichen planus: a systematic review and meta‐analysis

Abstract: This study was carried out to assess and compare the efficacy of tacrolimus and clobetasol in the treatment of oral lichen planus (OLP). The Cochrane Central Register of Controlled Trials, PubMed, Scopus, Science Direct, Springer Journals, and Elsevier databases were searched using specific keywords relevant to the research question for articles published from 1998 to December 31, 2012. Finally, 15 articles that assessed the effects of tacrolimus, clobetasol, and pimecrolimus on improvements in OLP were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 50 publications
1
49
0
1
Order By: Relevance
“…Given the obscure etiology, the management of OLP is challenging and the current treatment modalities are mainly focused to alleviate symptoms and eliminate mucosal erythema and ulcerations. Many different local and systemic therapeutic modalities have been tried to improve the lesions and reduce the associated pain . However, the results have been unsatisfactory and as yet there is no definite cure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the obscure etiology, the management of OLP is challenging and the current treatment modalities are mainly focused to alleviate symptoms and eliminate mucosal erythema and ulcerations. Many different local and systemic therapeutic modalities have been tried to improve the lesions and reduce the associated pain . However, the results have been unsatisfactory and as yet there is no definite cure .…”
Section: Introductionmentioning
confidence: 99%
“…Topical and systemic corticosteroids are the most widely accepted treatment modality for OLP . Nevertheless, due to the chronic nature of OLP, long‐term use of corticosteroids is associated with certain local and systemic complications that include mucosal atrophy, oral candidiasis, adrenal insufficiency, gastrointestinal disorders, hypertension, and diabetes …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared topical steroids, such as triamcinolone, with tacrolimus . However, a systematic review and meta‐analysis undertaken by Chamani et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, a systematic review and meta‐analysis undertaken by Chamani et al. identified only three clinical trials up to date which had directly compared tacrolimus with Clobetasol . Lack of consensus is evident as, two studies claim tacrolimus to be efficient, while Radfar et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to be an effective means of controlling the symptoms and signs of erosive or ulcerative oral lichen planus and had no notable adverse effects over a mean duration of application of 19.8 months [13]. In a meta analysis by Chamani G et al [14] it was concluded that topical Tacrolimus is an effective alternate to various corticosteroids and may be considered as a first line therapy in the management of OLEP.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%